2019
DOI: 10.1063/1.5064799
|View full text |Cite
|
Sign up to set email alerts
|

Post-collision hydrodynamics of droplets on cylindrical bodies of variant convexity and wettability

Abstract: Droplet impact, dynamics, wetting and spreading behavior on surfaces imposes rich and interesting physics, in addition to extensive understanding of processed employing droplets and sprays. The physics and mechnisms become richer and more interesting in the event the geometry, morphology and wettability of the surface provides additional constraints to the fluid dynamics. Post-impingement morphology and dynamics of water droplets on convex cylindrical surfaces of variant radii has been explored experimentally.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In Figure a, the restitution coefficients of all complete rebounds that we investigated are plotted as a function of the Weber number and the impact velocity. The scatter of the data shown in the figure is an inevitable phenomenon of experimental investigations of multiphase free-surface flows, including the impact of liquid droplets on solid surfaces, where the underlying hydrodynamics are very complex. , The scatter of the restitution coefficient at low Weber numbers is also enhanced by the existence of inevitable surface defects due to the dominant role of the droplet–surface friction in energy dissipation, though much care has been taken in the surface fabrication. Indeed, existing studies of bouncing droplets on hot surfaces above the Leidenfrost temperature ,, and on sublimation solid surfaces such as dry ice, , where the impinging droplets are always suspended on a thin gas layer without contact with the solid surfaces, reported weakly scattered experimental data of diverse impact characteristics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In Figure a, the restitution coefficients of all complete rebounds that we investigated are plotted as a function of the Weber number and the impact velocity. The scatter of the data shown in the figure is an inevitable phenomenon of experimental investigations of multiphase free-surface flows, including the impact of liquid droplets on solid surfaces, where the underlying hydrodynamics are very complex. , The scatter of the restitution coefficient at low Weber numbers is also enhanced by the existence of inevitable surface defects due to the dominant role of the droplet–surface friction in energy dissipation, though much care has been taken in the surface fabrication. Indeed, existing studies of bouncing droplets on hot surfaces above the Leidenfrost temperature ,, and on sublimation solid surfaces such as dry ice, , where the impinging droplets are always suspended on a thin gas layer without contact with the solid surfaces, reported weakly scattered experimental data of diverse impact characteristics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Extensive studies, therefore, have been reported on droplet impact on a planar substrate since the pioneering work by Worthington, but only limited works have been performed on a curved (spherical or cylindrical) surface. Among that, the droplet dynamics on a spherical substrate are relatively perspicuous owing to the regular annulus-symmetry of the fluid dynamics. Conversely, on a cylindrical surface, the corresponding impact dynamics are more complex since the substrate breaks down the annulus symmetry. Once a droplet touches the substrate, it would spread both in the axial and azimuthal directions, with the latter commonly being presented along the periphery extended from the impact point. By doing so, the droplet dynamics with rotational symmetry on a horizontal or spherical surface can be transformed into that with planar symmetry. Such impact is quite common in nature and various industrial processes, like raindrops hitting wires or liquid impinging nanotubes in a microfluidic chip, which has attracted increasing attention in recent years. , …”
Section: Introductionmentioning
confidence: 99%
“…where l c = encapsulation height (36) The energy due to viscous dissipation could be calculated by the Chandra and Avedisian 60 equation as follows (37) where volume of the viscous fluid…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Therefore, it has received plenty of attention from researchers. In recent years, the behaviors of drop impingement on curved substrates such as inclined, cylindrical, , convex, and spherical surfaces have been described thoroughly. The influence on these curved surfaces results in essential and problematic droplet properties in terms of spreading behavior.…”
Section: Introductionmentioning
confidence: 99%